2016
DOI: 10.1179/1476830515y.0000000043
|View full text |Cite
|
Sign up to set email alerts
|

Dietary recommendations for the prevention of depression

Abstract: Although there are a number of gaps in the scientific literature to date, existing evidence suggests that a combination of healthful dietary practices may reduce the risk of developing depression. It is imperative to remain mindful of any protective effects that are likely to come from the cumulative and synergic effect of nutrients that comprise the whole-diet, rather than from the effects of individual nutrients or single foods. As the body of evidence grows from controlled intervention studies on dietary pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(170 citation statements)
references
References 97 publications
3
141
1
4
Order By: Relevance
“…Instead of supplementing omega-3 fatty acids as discussed in the next paragraph, the most (physio)logical way to increase omega-3 fatty acid concentrations would be to eat more omega-3 fatty acids (e.g., fatty fish) and less omega-6 fatty acids. Several dietary trials are underway in psychiatric disorders, some already show potential of dietary modification, including increasing omega-3 fatty acid intake, e.g., from nuts and fish (Berk et al 2013;Sarris et al 2015;Opie et al 2016). For example, in depression, a relatively well-conducted 12-week single blind randomized controlled trial of an adjunctive dietary intervention vs. a social support protocol showed a number needed to treat of 4.1 for remission (Jacka et al 2017).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Instead of supplementing omega-3 fatty acids as discussed in the next paragraph, the most (physio)logical way to increase omega-3 fatty acid concentrations would be to eat more omega-3 fatty acids (e.g., fatty fish) and less omega-6 fatty acids. Several dietary trials are underway in psychiatric disorders, some already show potential of dietary modification, including increasing omega-3 fatty acid intake, e.g., from nuts and fish (Berk et al 2013;Sarris et al 2015;Opie et al 2016). For example, in depression, a relatively well-conducted 12-week single blind randomized controlled trial of an adjunctive dietary intervention vs. a social support protocol showed a number needed to treat of 4.1 for remission (Jacka et al 2017).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Fittingly, a set of dietary recommendations for the prevention of depression was recently issued by a group of Australian and European investigators. 24 These recommendations, however, do not seem to be specific to depression as they are similar to the general recommendations for a healthy diet. The recommendation to eat fruits and vegetables for the prevention of depression noted by Opie et al 24 is supported by the results of a recent meta-analysis of observational studies involving over 200,000 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…24 These recommendations, however, do not seem to be specific to depression as they are similar to the general recommendations for a healthy diet. The recommendation to eat fruits and vegetables for the prevention of depression noted by Opie et al 24 is supported by the results of a recent meta-analysis of observational studies involving over 200,000 individuals. 25 An earlier publication by Opie et al 26 concluded that “effective dietary interventions were based on a single delivery mode, employed a dietitian and were less likely to recommend reducing red meat intake, select leaner meat products or follow a low-cholesterol diet.” 26 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, preliminary prospective data indicate that the consumption of certain nutrients like red meat [196] and even milk [197] may confer a higher risk of developing depression. The recognition that diet is a key driver of gut health, as well as inflammation and oxidative stress, highlights the likely importance of the gut in mediating the association between diet and MDD [198] and points to the utility of targeting dietary quality to improve gut health and resulting disease states, including MDD [199,200] , IBS [201] , and metabolic disorders [202,203] . For instance, alterations in the abundance of Roseburia , which has been noted in MDD, IBS, CFS, and obesity [10,105,204,205] , can be decreased by low-fat, high-complex carbohydrate diets [206] .…”
Section: The Potential Of Dietary Change To Benefit Gut Permeability mentioning
confidence: 99%